The length of the biliopancreatic limb in one anastomosis gastric bypass - Focquet, Marc (Frontiers in Surgery, 2024)
Introduction The one-anastomosis gastric bypass (OAGB), first published by Dr Rutledge in 1997 is now a well-established procedure in the bariatric-metabolic armamentarium. This procedure based on a (single) loop gastro-jejunal anastomosis (the biliopancreatic limb or BPL) with a long narrow gastric pouch combines restriction with hypo-absorption. The biliopancreatic limb and in particular its length is held responsible for the degree of the hypo-absorptive effect but the most appropriate or “optimal” length of the BPL remains debatable. Methods The following text is based on a comprehensive and meticulous selection of the most recent literature in Cochrane, Pubmed and Google Scholar using the search terms “biliopancreatic limb”, "biliopancreatic limb in one anastomosis gastric bypass” in an attempt to define not only the most common used biliopancreatic limb length but also to find out If there is an “ideal” limb length not only to optimize the outcomes of the OAGB in terms of weight loss and resolution of obesity-related diseases but also to reduce the potential side-effects in particular nutritional deficiencies. Results Until today there is no consensus about the “standard” or “ideal” length of the biliopancreatic limb in OAGB, a fixed length of 200 cm is still the most common used procedure although many reports and studies are in favour of shorter limb lengths adjusted to the BMI or the total small bowel length. Conclusion The “ideal” or “optimal” biliopancreatic limb length in OAGB still needs to be defined. There are different options and all of them have their credits, the question remains if a consensus can be reached regarding the best strategy to obtain the best outcome.